Disease gene prioritization with quantum walks - Saarinen, Harto; Goldsmith, Mark; Wang, Rui-Sheng; Loscalzo, Joseph; Maniscalco, Sabrina (Oxford University Press, 2025)
Motivation: Disease gene prioritization methods assign scores to genes or proteins according to their likely relevance for a given disease based on a provided set of seed genes. This scoring can be used to find new biologically relevant genes or proteins for many diseases. Although methods based on classical random walks have proven to yield competitive results, quantum walk methods have not been explored to this end.
Results: We propose a new algorithm for disease gene prioritization based on continuous-time quantum walks using the adjacency matrix of a protein–protein interaction (PPI) network. We demonstrate the success of our proposed quantum walk method by comparing it to several well-known gene prioritization methods on three disease sets, across seven different PPI networks. In order to compare these methods, we use cross-validation and examine the mean reciprocal ranks of recall and average precision values. We further validate our method by performing an enrichment analysis of the predicted genes for coronary artery disease.
Availability and implementation: The data and code for the methods can be accessed at https://github.com/markgolds/qdgp.